A Sharp Estimate of a Simplified Viscosity Splitting Scheme (Journal of Computational Mathematics, 1993)
A viscosity splitting method for solving the initial boundary value problems of the Navier-Stokes equation, introduced by Zheng and Huang, is considered. We give an improved and sharp estimate in the space $L^{∞}(0,T;(L^2(Ω))^2)$.